Thermodynamic behaviour of undercooled melts - Mishra R.K.; Dubey K.S. (My University, 2025)
The Gibbs free energy difference (ΔG) between the undercooled liquid and the equilibrium solid phases has been studied for the various kinds of glass forming melts such as metallic, molecular and oxides melts using the hole theory of liquids and an excellent agreement is found between calculated and experimental values of ΔG. The study is made for non-glass forming melts also. The temperature dependence of enthalpy difference (ΔH) and entropy difference (ΔS) between the two phases, liquid and solid, has also been studied. The Kauzmann temperature (To) has been estimated using the expression for ΔS and a linear relation is found between the reduced glass transition temperature (Tg/Tm) and (To/Tm). The residual entropy (ΔSR) has been estimated for glass forming melts and an attempt is made to correlate ΔSD, Tg, To, and Tm which play a very important role in the study of glass forming melts.